Sustaining Trade Reform : Institutional Lessons from Argentina and Peru - Baracat, Elias A.; Finger, J. Michael; Thorne, Raúl León; Nogués, Julio J. (Washington, DC: World Bank, 2013)
Trade reform in Latin America in the 1980s and 1990s was in significant part a reform of policy-making institutions. The institutions that existed when the reforms began had been created in response to particular protectionist pressures at particular times, and afterward they were controlled by the interests on whose behalf they had been created. This book was prompted by preliminary evidence suggesting that the reforms have been better sustained in Peru than in Argentina. Peru has continued its liberalization whereas Argentina has imposed a number of new trade restrictions. Moreover, decisions on many of Argentina's restrictions have not gone through the new mechanisms. The objective of this book is to draw lessons from Peruvian and Argentine experience that will be useful to governments that want to maintain an open trade regime. From a positive perspective, the authors want to identify what the Peruvian government has done that has kept its liberalization moving forward. The Peru study focuses on how reform leaders in that country have reinforced the evolution of a new management culture and how they have disseminated widely in Peruvian society a positive vision of Peru in the international economy.